Anti-recurrent therapy of chronic VVC: realities and perspectives - Т. Ф Татарчук; Л. В. Калугина (Publishing House TRILIST, 2017)
Chronic recurrent vulvovaginal candidiasis (VVC) occurs in 50% of women of childbearing age, while 20-50% of women in the normal microflora of the vagina determine fungi of the genus Candida without manifestation of clinical symptoms. To date, the search for schemes of VVC anti-recurrent therapy was carried out mainly in the aspect of the use of oral anti-mycotics. However, taking into account their potential toxicity and drug load on patients at the groups of risk, the authors of the article note that it is most expedient to use local preparations. The article presents the results of local therapy of chronic recurrent VVC by fenticonazole nitrate (drug Lomexin®) according to the proposed optimized scheme. The study involved 60 patients 18-45 years old, who were divided into 2 equal groups of 30 women. Patients of both groups were prescribed a basic treatment regimen: capsules of Lomexin® at a dose of 1000 mg for the 1st and 4th days on night intravaginally. In the course of further observation, the women of the main group received 600 mg of the drug once before the menstruation for 3 consecutive cycles. Women of the comparison group did not receive an anti-recurrent course. Assessment of symptoms of recurrent VVC was carried out after the end of menstrual cycle of the 5th month of observation in both groups. The experience of local therapy of chronic VVC with a double dose of fenticonazole showed both high efficacy of the drug for topical use and compliance of this scheme. In particular, at the end of the basic therapy, the itching in the genital area ceased to disturb 95% of the patients. Excretas, which before treatment was noted by all patients, were concerned only 5% of those surveyed after therapy. Conduction of anti-recurrent therapy with capsules of Lomexin® 600 mg during 3 cycles once allowed to reduce the number of recurrence of VVC episodes to 2 (6.9%) of clinically pronounced cases, with symptomatology having a mild character. The proposed scheme of anti-relapse therapy makes it possible to significantly reduce the frequency of recurrent episodes of the disease, which indicates its higher (93.1%) effect compared with the observation group (71.43%). The effectiveness of this scheme is extremely important for the local therapy of chronic VVC when choosing a drug for the treatment of patients with extragenital pathology, especially if there are contraindications to systemic therapy.